Bamboo Utilization in the Peleng Island: Unveiling Local Knowledge and Diverse Applications - Damayanto, I Putu Gede P.; Susila (BIODIVERS - BIOTROP Science Magazine, 2024)
Bamboo is a useful plant that holds significant cultural and economic importance, particularly in small Indonesian islands like Peleng Island in Central Sulawesi. This paper explores bamboo utilization on Peleng Island, aiming to broaden our understanding of bamboo use on small Indonesian islands and shed light on local wisdom in bamboo utilization. The research was conducted on Peleng Island in 2019. Information on bamboo utilization was gathered through in-depth interviews with residents. Bamboo materials were collected and sent to the Herbarium Bogoriense for identification. The data were analysed descriptively. There are six bamboo species utilized on Peleng Island, namely Bambusa vulgaris, Dendrocalamus asper, Gigantochloa atter, Neololeba atra, Schizostachyum brachycladum, and Schizostachyum lima. Bamboo on Peleng Island is used for building materials (roofs, pillars, and wall weaving), cooking traditional foods like nasi jaha and bambu suman, and for various other uses (ornamental plants, water containers, stairs, poles for picking fruits/cloves, pest traps, and fish trap).